Investigation of Differences Among Grain Hybrid Corn Varieties in Terms of Yield and Quality Characteristics - Abdullah Nas; İsmail Karakaş; Fatma Aykut Tonk (Acta Natura et Scientia)
This study was carried out to determine the yield, yield parameters and quality characteristics of different grain hybrid corn varieties in Ovaköy ecological conditions of Balıkesir/Altıeylül district as the main crop in 2022. A total of ten different grain hybrid corn varieties were used as plant material in the study. The experiment was established according to the randomized block design with three replications. Among the yield and yield characteristics examined in the study; plant height varied between 2.37-2.99 m, plant stem thickness between 20.93-24.47 mm, ear length between 16.56-21.57 cm, ear diameter between 4.77-5.29 cm, grain to ear ratio between 0.86-0.95%, number of grains per ear between 527.67-746.65 pieces, grain yield between 193.33-284.41 g/plant, thousand grain weight between 362.00-468.67 g. Quality characteristics in the study; grain moisture varied between 20.73-24.33%, grain starch ratio between 67.84-71.46%, hectoliter weight between 73.60-76.33 kg, ash value between 1.04-1.22%, protein ratio between 8.25-9.25%, cellulose ratio between 2.15-2.28% and oil ratio between 2.20-2.67%. DKC 6980 and SY Bambus stood out among the varieties examined in the research regarding plant yield, cob length, cob diameter, number of grains per cob, hectoliter weight and protein ratio.